Quality of life of women with polycystic ovarian syndrome - Dey, Prabha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Polycystic ovary syndrome (PCOS), also known as hyper androgenic anovolation (HA or Stein-Leventhal syndrome) is a well-recognised and common condition that causes considerable morbidity. The objective of the present study was to find out the quality of life of women with polycystic ovarian syndrome. Methods: Patients with PCOD diagnosed clinically at out patients department were selected for the study. SF 36 was applied to find out the Quality of life of women with polycystic ovarian syndrome. Results: A total of 84 patients were participated and 75% of the sample were student, 56.7% were graduate and 86.7% were non-vegetarian. The mean height of the sample was 155±4.81 centimeters. The mean weight of sample was 59.35±6.63 kgs and BMI mean was 24.70±3.47. Among 35% the duration of diagnosis was less than one year and for 65% it was more than one year. Means of the all sub set scores, across shorter and longer duration of being diagnosed as PCOD were significantly same on t test. Conclusions: Measured by SF 36, women with poly cystic ovarian disease/symptoms are suffering from significantly lowered quality of life, but independent of their duration of illness.